2019
DOI: 10.3389/fgene.2019.01025
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Multi-Cohort Approach Reveals Novel and Known Genome-Wide Selection Signatures for Wool Traits in Merino and Merino-Derived Sheep Breeds

Abstract: Merino sheep represents a valuable genetic resource worldwide. In this study, we investigated selection signatures in Merino (and Merino-derived) sheep breeds using genome-wide SNP data and two different approaches: a classical FST-outlier method and an approach based on the analysis of local ancestry in admixed populations. In order to capture the most reliable signals, we adopted a combined, multi-cohort approach. In particular, scenarios involving four Merino breeds (Spanish Merino, Australian Merino, Chine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 97 publications
3
22
0
2
Order By: Relevance
“…The ROH hotspot with highest SNP occurrence was located on OAR6 , which consisted of the NCAPG/LCORL gene. Similar findings were also reported in Italian sheep breeds [22], Spanish sheep breeds [21], Swiss sheep breeds, and Merino [18,31]. Moreover, the selective signatures in NCAPG/LCORL region were found in many sheep breeds [18,32,33], including Merino [34].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The ROH hotspot with highest SNP occurrence was located on OAR6 , which consisted of the NCAPG/LCORL gene. Similar findings were also reported in Italian sheep breeds [22], Spanish sheep breeds [21], Swiss sheep breeds, and Merino [18,31]. Moreover, the selective signatures in NCAPG/LCORL region were found in many sheep breeds [18,32,33], including Merino [34].…”
Section: Discussionsupporting
confidence: 85%
“…GWAS results demonstrated that RXFP2 region was associated with horn phenotype in sheep [49]. The selective sweep region harbouring RXFP2 was also identified in Merino [31], and this region was successfully used to predict the horned and polled phenotypes in Merino [50,51]. Additionally, the recombination rate on this genome region was relatively high.…”
Section: Discussionmentioning
confidence: 93%
“…For instance, EXT1 located on OAR9 include the SNPs (75.5 Mb, p = 5.68E-07) was associated with FD near a known QTL (75.9 Mb) [ 10 ]. PAX9 located on OAR18, which include the SNPs (45.6 Mb, p = 8.13E-07), was identified to be related to hair defects [ 30 ]; this finding agrees with the genome-wide selection signatures for wool traits among Merino and Merino-derived sheep breeds [ 31 ]. KRT17 located on OAR11, which is near the SNPs (41.2 Mb, p = 1.34E-06), is required for the correct growth of hair follicles, especially for continuous growth [ 32 ].…”
Section: Discussionsupporting
confidence: 64%
“…In this study, we (i) pair-wise contrasted 15 "grey" cattle breeds each versus four "non-grey" cattle breeds; (ii) retained, for each pair-wise contrast, loci with q-value < 0.05 assumed to be putatively under selection; and (iii) applied an arbitrary and intentionally loose (to account for genetic heterogeneity of the considered breeds) across-scenario multi-occurrence threshold (25%). We previously demonstrated the robustness of a similar multi-cohort framework in a study for identification of selection signatures in Merino (and Merino-derived) sheep breeds contrasted with breeds that had no known Merino genetic background [40]. In this study, using the above-described approach, the highly supported selection signature at chromosome 14 mentioned above was identified.…”
Section: The Multi-cohort F St -Outlier Methods Is a Robust Approach Fmentioning
confidence: 79%